The Ukrainian Economy Tendencies in the Context of the Global Crisis (Study on the Basis of Business Tendency Surveys) - Pugachova, Maryna (Lithuanian Journal of Statistics, 2013)
This article discusses the possibilities to study the economy in times of crisis and its post-crisis performance by use of selected indicators from the Business Tendency Survey. Unlike conventional statistical indicators, these indicators can give quick information about the opinions, judgments and expectations of enterprise managers concerning their company's performance, which allows the drawing of conclusions about business operation by economic activity, sector and the whole economy. The analysis is made by use of several indicators from Ukrainian surveys: change in the competition; production capacities utilization and wear; factors limiting enterprises’ development. The analysis is made by economic sector: industry, construction and transport.
Keywords: conjuncture (business tendency) surveys of enterprises (BTS); indicators of enterprises’ business activity; competitiveness in branches of economy; capacity utilization